2016
DOI: 10.1136/vr.103916
|View full text |Cite
|
Sign up to set email alerts
|

Survey of veterinary antimicrobial prescribing practices, Washington State 2015

Abstract: Antimicrobial resistance is a growing global health issue. It is also a recognised problem in veterinary medicine. Between September and December 2015 the authors administered a cross-sectional survey to licensed veterinarians in Washington State to assess factors affecting antimicrobial prescribing practices among veterinarians in Washington State. Two hundred and three veterinarians completed the survey. The majority of respondents (166, 82 per cent) were engaged in small animal or exotic animal practice. 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 39 publications
(56 reference statements)
4
41
3
Order By: Relevance
“…the north western United States cost of culture and sensitivity was a commonly listed barrier (43). The antimicrobial use guidelines for UTI were recently updated (17) and incorporate a change in the recommended duration of antimicrobial therapy to 3-5 days rather than 7-10 days previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…the north western United States cost of culture and sensitivity was a commonly listed barrier (43). The antimicrobial use guidelines for UTI were recently updated (17) and incorporate a change in the recommended duration of antimicrobial therapy to 3-5 days rather than 7-10 days previously suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Mateus et al (2014) [8] also highlighted factors related to diagnostic use as important influences on decision-making in antibiotic prescribing. Studies have shown that the rate of use of laboratory tests to support prescribing decisions can be very low [14–16]. Eschler and colleagues (2011) [14] found that only 3.7% cases of fluoroquinalone prescriptions for companion animals were supported with laboratory testing; and only around half of the respondents in Hughes and colleagues (2012) [15] survey of antimicrobial prescribing patterns in small animal practice identified laboratory tests to be an important influence on their antimicrobial decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract disease is a common indication for antimicrobial prescribing in small animal veterinary practices. However, given the cost of QBC and financial limitations of owners, urinary tract infection (UTI) diagnoses are inconsistently confirmed . Routine use of QBC and susceptibility testing in dogs and cats with suspected UTIs supports antimicrobial stewardship by guiding effective treatment and allowing veterinarians to monitor for antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative bacterial culture (QBC) and susceptibility testing with concurrent urinalysis are the gold standard for diagnosing infection and selecting treatment. Cost is the most common barrier cited by veterinarians to performing QBC . When a urine QBC is recommended, veterinarians and owners should have assurance of the reliability and diagnostic utility of the test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation